2022
DOI: 10.1111/1748-8583.12469
|View full text |Cite
|
Sign up to set email alerts
|

Career satisfaction in the public sector: Implications for a more sustainable and socially responsible human resource management

Abstract: Anchored in emerging theoretical insights regarding sustainable human resource management, with a focus on pursuing socially responsible HR, we propose that enhancing employees' career satisfaction in public sector organisations constitutes a unique opportunity for public sector organisations to improve their internal social responsibility, focussing on employees as key stakeholders. In this context, this study provides original evidence regarding an original framework for examining the determinants and outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 112 publications
(171 reference statements)
0
5
0
Order By: Relevance
“…The common conceptualization of sustainable HRM involves integrating the social, environmental, and economic goals of organizations (Bush, 2020). Recently, management scholars have come to focus on the role played by two types of sustainable HRM in influencing employee behaviors: “socially” responsible HRM (e.g., Latan et al., 2022; Shen & Benson, 2016) and green HRM (e.g., Dumont et al., 2017). However, in light of several recent complex and significant global challenges, it has become clear that a sustainable HRM strategy requires a new approach—common good HRM (CGHRM)—that reverses the perspective of the management model from inside‐out (as is the case in traditional approaches) to outside‐in (Aust et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The common conceptualization of sustainable HRM involves integrating the social, environmental, and economic goals of organizations (Bush, 2020). Recently, management scholars have come to focus on the role played by two types of sustainable HRM in influencing employee behaviors: “socially” responsible HRM (e.g., Latan et al., 2022; Shen & Benson, 2016) and green HRM (e.g., Dumont et al., 2017). However, in light of several recent complex and significant global challenges, it has become clear that a sustainable HRM strategy requires a new approach—common good HRM (CGHRM)—that reverses the perspective of the management model from inside‐out (as is the case in traditional approaches) to outside‐in (Aust et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…• Provision of opportunities for career building and development of human potential through the creation of knowledge-intensive jobs, with creative activities and innovative activity of employees (Diaz-Carrion et al, 2019;Latan et al, 2022;Rawshdeh et al, 2019;Zhang et al, 2015), as well as the creation of highly productive jobs, which imply the use of the leading technologies and automatization means, in particular, the support of decent jobs for digital personnel (Ramos-González et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, EE plays a pivotal role in driving CSR within organizations. By nurturing EE and endorsing sustainable business practices, organizations can elevate their social and environmental impact, enhance overall organizational performance and contribute to a more sustainable future (Latan et al, 2022). Moreover, an examination of the literature on QWL reveals the influence of EE on QWL.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, Stepansky et al (2022) explored the impact of green spaces on employees' QWL in a university environment, finding a positive correlation between engagement and quality of work life. Several studies on nurse engagement and burnout have also revealed a negative correlation between QWL and burnout, as well as a positive correlation between QWL and work engagement (Sun et al, 2022;Remegio et al, 2021;Latan et al, 2022). Consequently, EE has been extensively discussed in the literature on employees' QWL.…”
Section: Literature Reviewmentioning
confidence: 99%